Does maternity during sports career jeopardize future athletic success in elite marathon runners? - Forstmann, N.; Meignié, A.; De Larochelambert, Q.; Duncombe, S.; Schaal, K.; Maître, C.; Toussaint, J.-F.; Antero, J. (European Journal of Sport Science, 2023)
The impact of maternity (Mat) on subsequent athletic performance is not well known. This study aims to investigate the impact of maternity among elite marathoners on their overall performance progression. For each runner listed in the top 150 female marathoners, who had experienced a mid-career maternity, performance development was reconstituted throughout the career. Maternity data and career break time span (Ttotal) were collected from publicly available informations. Performances were modelled according to the known age-performance relationship and the impact of maternity was added into the model. Linear mixed effect model was used to study the influence of maternity on the overall career. Among this sample, 37 runners had at least 1 child during her career. Among them, 14 had 2 children. Eleven runners (29.72%) made their personal best performance before Mat, which occurred at an average age of 28.40 ± 4.00 years. Twenty-six runners (70.28%) establish their best performances after Mat, at an average age of 32.20 ± 4.28. The age-performance relationship model explains 92% of the performance variability during the career`s progression. When age is considered, maternity does not have significant impact on performance development. World`s most competitive marathoners can still perform at their best level after pregnancy. The ability to return and surpass previous performance level is influenced by the age at which pregnancy occurs, relative to the age of peak performance during career development.